2016
DOI: 10.1590/1982-02752016000400004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico de malformações congênitas: impactos sobre a saúde mental de gestantes

Abstract: ResumoMalformação congênita, segunda maior causa de mortalidade infantil, constitui condição de vulnerabilidade importante na gravidez, que repercute desfavoravelmente na saúde mental da gestante. Objetivou-se estudar o impacto do momento do diagnóstico de malformação congênita sobre a saúde mental de 66 gestantes em atendimento pré-natal. Para isso, as participantes responderam ao Questionário "Momento da notícia", o qual identifica variáveis psicossociais relativas ao momento do diagnóstico da deficiência, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
29

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 10 publications
1
13
0
29
Order By: Relevance
“…The news of the malformation in the first trimester showed association with anxiety. The number of pregnant women with signs of moderate anxiety (23%) also deserves attention 1 , which corroborates with the findings of the present study, in which 53.9% and 47% of the mothers investigated had moderate anxiety levels in both the IDATE-Trait and in the IDATE-State evaluation. Another research carried out in two cities in the interior of São Paulo state aimed at evaluating how maternal-fetal attachment is established, the coping modes, the clinical indicators and anxiety and depression in the prenatal phase in pregnant women who had received the diagnosis of the congenital malformation showed that the scores for anxiety were high.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The news of the malformation in the first trimester showed association with anxiety. The number of pregnant women with signs of moderate anxiety (23%) also deserves attention 1 , which corroborates with the findings of the present study, in which 53.9% and 47% of the mothers investigated had moderate anxiety levels in both the IDATE-Trait and in the IDATE-State evaluation. Another research carried out in two cities in the interior of São Paulo state aimed at evaluating how maternal-fetal attachment is established, the coping modes, the clinical indicators and anxiety and depression in the prenatal phase in pregnant women who had received the diagnosis of the congenital malformation showed that the scores for anxiety were high.…”
Section: Discussionsupporting
confidence: 91%
“…Gestation is a phase of transition in the life of the woman in which, from the moment of fertilization until birth, the pregnant woman and the baby go through unique psychological, physiological and social experiences, causing the woman to have doubts and expectations in relation to the new being that is yet to be born and to the role she will have to assume 1 - 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os dados corroboram com os achados por Saviani- Zeoti 20 , no qual gestantes em situações de vulnerabilidade para si mesma e seu feto apresentam índices de ansiedade mais elevados. O nível de ansiedade pode aumentar quando existe possibilidade ou mesmo quando se apresenta o risco para uma anomalia ou malformação fetal, podendo a ansiedade prolongar-se até o período pós-natal 21 .…”
Section: Resultsunclassified
“…In view of this situation, the pregnant woman experiences very negative feelings, in addition to the fact that the anencephalic gestation itself can lead to physical complications, such as polyhydramnios, births with dystocia, hypertensive diseases, severe psychological conditions, among others 5 . There is a rupture with the expectation of the idealized and perfect child, which translates into a moment of intense emotional distress and anguish in most cases and the complex decision to interrupt or not to interrupt the pregnancy becomes real 9 .…”
Section: Introductionmentioning
confidence: 99%